ANALYSIS OF SPATIAL ASPECTS OF MEDAN TELADAN STADIUM RENOVATION - Hendra Fahruddin Siregar (Lembaga Pengembangan Kinerja Dosen, 2022)
Based on the purpose of the Feasibility Study on the Renovation of the Medan City Exemplary Stadium, is to obtain a Foundation for the Planning and Design Program regarding the Renovation of the Exemplary Stadium in Medan City which has supporting facilities and is worthy of national fit. Spatial aspects in the feasibility study of the renovation of the Medan City Exemplary Stadium are adjusted to Regional Regulation No.1 of 2022 of the city of Medan (Regional Spatial Plan 2022 to 2042). The feasibility study of the renovation of the Medan City Exemplary Stadium used quantitative descriptive research, with the data used were primary data and secondary data. The Feasibility Study Method of Exemplary Stadium Renovation Planning to explain the design requirements (design needs) and design determinants related to the planning and design of the Exemplary Football Stadium with the analysis of spatial aspects. The results of this study are reviewed from the aspect of spatial planning, so the concept planned for the renovation of the Exemplary Stadium is feasible to be implemented.